2014
DOI: 10.1517/14656566.2014.960389
|View full text |Cite
|
Sign up to set email alerts
|

Current pharmacotherapy for treating pediatric nonalcoholic fatty liver disease

Abstract: Considering the multifactorial pathogenesis and the wide spectrum of histological and clinical features of NAFLD, we believe that a drug mix, containing agents that are effective against the principal pathogenetic factors, associated with lifestyle modification, could represent the winning choice of treatment for pediatric NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Further validation of TE is necessary before it can be routinely adopted for the evaluation of NAFLD in childhood [14,15]. Novel therapeutic strategies have been tested in the last years with interesting results [16]. The drugs initially used in treatment of NAFLD, such as anti-oxidants (vitamin E), insulin-sensitizing (metformin) and cytoprotective agents (ursodeoxycholic acid -UDCA) have given disappointing results, with only limited effects, and, therefore, to date there is no definitive treatment for pediatric NAFLD.…”
Section: Nafldmentioning
confidence: 99%
“…Further validation of TE is necessary before it can be routinely adopted for the evaluation of NAFLD in childhood [14,15]. Novel therapeutic strategies have been tested in the last years with interesting results [16]. The drugs initially used in treatment of NAFLD, such as anti-oxidants (vitamin E), insulin-sensitizing (metformin) and cytoprotective agents (ursodeoxycholic acid -UDCA) have given disappointing results, with only limited effects, and, therefore, to date there is no definitive treatment for pediatric NAFLD.…”
Section: Nafldmentioning
confidence: 99%
“…Unfortunately, DHA showed no effect on liver fibrosis, with amelioration of steatosis, ballooning and lobular inflammation. Based on these promising results and the optimal safety profile, DHA represents a useful option in the treatment of pediatric NAFLD (4).…”
mentioning
confidence: 99%
“…The data available for pediatric NAFLD suggested that probiotics warrant consideration as an additional beneficial therapy in these patients, demonstrating a positive effect on echographic liver steatosis, amino- transferases serum levels and BMI; in addition, a positive effects on markers of inflammation and metabolic parameters, as cholesterol-low density lipoprotein (LDL) and insulin-resistance, were reported in adults treated with a mixture of probiotics (4). Based on the advances in pathogenetic mechanisms of NAFLD/NASH, several molecular pathways have been identified as possible targets of novel treatment for NAFLD.…”
mentioning
confidence: 99%